Silicon Nanomaterials for Biosensing and Bioimaging Analysis - Ji, Xiaoyuan; Wang, Houyu; Song, Bin; Chu, Binbin; He, Yao (Frontiers in Chemistry, 2018)
Biochemical analysis in reliable, low-toxicity, and real-time manners are essentially important for exploring and unraveling biological events and related mechanisms. Silicon nanomaterial-based sensors and probes have potentiality to satisfy the above-mentioned requirements. Herein, we present an overview of the recent significant improvement in large-scale and facile synthesis of high-quality silicon nanomaterials and the research progress of biosensing and bioimaging analysis based on silicon nanomaterials. We especially illustrate the advanced applications of silicon nanomaterials in the field of ultrasensitive biomolecular detection and dynamic biological imaging analysis, with a focus on real-time and long-term detection. In the final section of this review, we discuss the major challenges and promising development in this domain.